Telaah Atas Ijtihad Umar Bin Khaṭṭab Perspektif Maqāṣid Al-Syarī'ah - Amir Sahidin (Jurnal Penelitian Medan Agama, 2023)
In the course of Islamic law, there were several issues of muamalat that were not found in law at the time of the Prophet, so the companions made ijtihad to find them. In fact, not infrequently the laws set by the companions seemed to contradict the teachings of the Prophet. As ijtihad was carried out by Umar bin Khaṭṭab in several ways such as: aborting the had punishment for adulterers, aborting the punishment for cutting off the hands of thieves, stopping giving zakat to mu'allaf, not dividing spoils of war between Muslim soldiers. Regarding some of these ijtihad, many people praised Umar's intelligence in grounding Islamic law. However, there are also some scholars who make Umar the pioneer of sharia deconstruction. This article attempts to examine Umar's ijtihad with the maqāṣid al-syarī'ah approach. Through research of the type of library research with a descriptive-analytic approach, it can be concluded that, first: Umar's ijtihad in some of the above cases did not actually deconstruct Islamic law, but because of his intelligence and foresight in seeing the factors that could hinder the implementation of these lawsuits. Second: Umar bin Khaṭṭab saw the naṣ textually and contextually in a balanced way, without annulling the existing naṣ.